1999
DOI: 10.1046/j.1365-2672.1999.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Nisin and ALTATM 2341 inhibit the growth ofListeria monocytogeneson smoked salmon packaged under vacuum or 100% CO2

Abstract: ) log 10 cfu g −1 at 10°C. With the ALTA TM 2341-treated samples, L. monocytogenes increased by 2·8 (0·1%) or 1·6 (1·0%) log 10 cfu g −1 at 4°C, and 3·3 (0·1%) or 3·6 (1·0%) log 10 cfu g −1 at 10°C. The growth of L. monocytogenes was retarded by packaging the smoked salmon in 100% CO 2 . On untreated smoked salmon, only a 0·8 log 10 cycle increase was observed at 10°C. Under all the other conditions tested with 100% CO 2 , L. monocytogenes was detected but growth was prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 15 publications
0
25
0
2
Order By: Relevance
“…Cahill (1998, 1999) evaluated the combined effects of a modified atmosphere (N 2 , CO 2 ), temperature (4 and 12°C), nisin and ALTA 2341 on the growth of L. monocytogenes isolates of food, human, and environmental origin on culture media (Szabo and Cahill 1998). The same authors also tested the growth of L. monocytogenes in smoked salmon packaged under vacuum or 100% CO 2 (Szabo and Cahill 1999). In both cases, these authors found that treatment with bacteriocins combined with a 100% CO 2 atmosphere prevented the growth of L. monocytogenes.…”
Section: Nisin Has Been Evaluated As An Antimicrobial Againstmentioning
confidence: 97%
“…Cahill (1998, 1999) evaluated the combined effects of a modified atmosphere (N 2 , CO 2 ), temperature (4 and 12°C), nisin and ALTA 2341 on the growth of L. monocytogenes isolates of food, human, and environmental origin on culture media (Szabo and Cahill 1998). The same authors also tested the growth of L. monocytogenes in smoked salmon packaged under vacuum or 100% CO 2 (Szabo and Cahill 1999). In both cases, these authors found that treatment with bacteriocins combined with a 100% CO 2 atmosphere prevented the growth of L. monocytogenes.…”
Section: Nisin Has Been Evaluated As An Antimicrobial Againstmentioning
confidence: 97%
“…The shelf life of vacuum packaged CSS kept under refrigerated conditions ( 4 C) is generally 3e5 weeks, as indicated by the producers (Leroi, Arbey, Joffraud, & Chevalier, 1996Rørvik et al, 1991). However, modified atmosphere packaging (MAP) has shown to improve shelf life compared to vacuum packaging in some studies (Cakli, Kilinc, Dincer, & Tolasa, 2006;Hansen et al, 2009;Paludan-Muller, Dalgaard, Huss, & Gram, 1998;Szabo & Cahill, 1999). A gas mixture of 70% CO 2 , 25% N 2, and 5% O 2 gave promising results for sliced CSS with respect to microbial, chemical, and sensory evaluation compared to mixtures with either more or less CO 2 (Civera, Amerio, & Parisi, 1993).…”
Section: Packaging and Storagementioning
confidence: 98%
“…Bacteriocins have a long history of use in dairy or meat applications and there is an increasing number of studies on the effect of bacteriocins as antimicrobials in the seafood industry (Table 5) (Aasen et al, 2003;Al-Holy et al, 2004;Budu-Amoako et al, 1999;Einarsson & Lauzon, 1995;Elotmani & Assobhei, 2004;Luders et al, 2003;Neetoo et al, 2008;Nilsson et al, 1997;Nykanen et al, 2000;Szabo &Cahill, 1999;Tahiri et al, 2009;Tsironi & Taoukis, 2010;Zuckerman & Ben Avraham, 2002). These studies have focused largely on the effects of nisin, a Gram-positive bacteriocin that has been generally recognized as safe (GRAS) by the FDA.…”
Section: Current Practices In the Seafood Industry To Combat Spoilagementioning
confidence: 99%
“…For example, bacteriocins can be impregnated into gel coatings and/or polyethylene films and can be applied to seafood during packaging (Neetoo et al, 2008). The application of bacteriocins on packaged seafood is steadily being seen as a very promising biopreservation method (Aasen et al, 2003;Al-Holy et al, 2004;Budu-Amoako et al, 1999;Einarsson & Lauzon, 1995;Elotmani & Assobhei, 2004;Luders et al, 2003;Neetoo et al, 2008;Nilsson et al, 1997;Nykanen et al, 2000;Szabo &Cahill, 1999;Tahiri et al, 2009;Tsironi & Taoukis, 2010;Zuckerman & Ben Avraham, 2002). In fact, immobilization of bacteriocins on coating materials for biopreservation may actually reduce the cost of packaging due to the reduced amount and cost of the antibacterial needed to attach to the film (Galvez et al, 2008).…”
Section: Bacteriocin Potential In the Seafood Industrymentioning
confidence: 99%